The Role of Bhabinkamtibmas in Solving Informed Citizens' Problems Regarding Community Trust in the Madiun City Police Area - Putra, I Made Sudarma (Indonesian Journal of Police Studies, 2024)
This research is based on the background of the high number of problems of inmates which are resolved by Bhabinkamtibmas through problem solving and followed by the results of the analysis of the Community Trust Index (IKM) of the National Police's performance in the five technical functions around the island of Java, one of the technical functions, namely Binmas, has value. IKM is the lowest compared to other technical functions in the East Java Regional Police in 2023. The aim of this research is to describe the role of Bhabinkamtibmas in solving social problems, find factors that influence the implementation of problem solving for inmates and describe the relationship between the performance of Bhabinkamtibmas in solving problems for inmates and community trust in the Madiun City Police. This research uses quantitative and qualitative methods. This research uses a combined research method, namely research based on a combination of Positivism and Posotivism. Data was collected using questionnaire and interview techniques. The theories used are Role Theory, SWOT, Performance, Public Trust and the concepts used in this research include the concepts of Bhabinkamtibmas and Problem Solving. The role of Bhabinkamtibmas is as a mediator in resolving the problems of the inmates. There are several internal and external factors that influence a Bhabinkamtibmas in resolving the problems of the inmates, namely those originating from within and outside the institution. From within (internal) includes strengths and weaknesses, while from outside (external) includes opportunities and threats and the performance of a Bhabinkamtibmas can influence public trust in the jurisdiction of a Police agency.